Functionalization of Ti-40Nb implant material with strontium by reactive sputtering - Markus Göttlicher; Marcus Rohnke; Yannik Moryson; Jürgen Thomas; Joachim Sann; Anja Lode; Matthias Schumacher; Romy Schmidt; Stefan Pilz; Annett Gebert; Thomas Gemming; Jürgen Janek (Biomaterials Research, 2017)
Abstract Background Surface functionalization of orthopedic implants with pharmaceutically active agents is a modern approach to enhance osseointegration in systemically altered bone. A local release of strontium, a verified bone building therapeutic agent, at the fracture site would diminish side effects, which could occur otherwise by oral administration. Strontium surface functionalization of specially designed titanium-niobium (Ti-40Nb) implant alloy would provide an advanced implant system that is mechanically adapted to altered bone with the ability to stimulate bone formation. Methods Strontium-containing coatings were prepared by reactive sputtering of strontium chloride (SrCl2) in a self-constructed capacitively coupled radio frequency (RF) plasma reactor. Film morphology, structure and composition were investigated by scanning electron microscopy (SEM), time of flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy (XPS). High-resolution transmission electron microscopy (HR-TEM) was used for the investigation of thickness and growth direction of the product layer. TEM lamellae were prepared using the focused ion beam (FIB) technique. Bioactivity of the surface coatings was tested by cultivation of primary human osteoblasts and subsequent analysis of cell morphology, viability, proliferation and differentiation. The results are correlated with the amount of strontium that is released from the coating in biomedical buffer solution, quantified by inductively coupled plasma mass spectrometry (ICP-MS). Results Dense coatings, consisting of SrOxCly, of more than 100 nm thickness and columnar structure, were prepared. TEM images of cross sections clearly show an incoherent but well-structured interface between coating and substrate without any cracks. Sr2+ is released from the SrOxCly coating into physiological solution as proven by ICP-MS analysis. Cell culture studies showed excellent biocompatibility of the functionalized alloy. Conclusions Ti-40Nb alloy, a potential orthopedic implant material for osteoporosis patients, could be successfully plasma coated with a dense SrOxCly film. The material performed well in in vitro tests. Nevertheless, the Sr2+ release must be optimized in future work to meet the requirements of an effective drug delivery system.